Analysing the sustainability of an art career from the caregivers' experiences and perspective for autistic individuals / Izza Syahida Abdul Karim ... [et al.] - Abdul Karim, Izza Syahida; Wan Omar, Wan Noor Faaizah; Anuar, Azyyati; Ahmad Zawawi, Azlyn (Universiti Teknologi MARA, Kedah, 2025)
This study examines the sustainability of art careers for autistic individuals by exploring the experiences and perspectives of caregivers, shedding light on the challenges and opportunities within this unique career path. Utilising a qualitative methodology, the research involved thematic analysis of interviews and observations, categorised into nine themes: Early Interest and Skill Development in Art, Art as a Means of Communication and Expression, Sensory Issues and Adaptations in Art, Techniques and Mediums in Art, Autonomy in Artistic Decisions, Participation in Art Activities and Programs, Exploration of Other Art Forms and Interests, Marketing and Support for Artistic Endeavours, and Benefits of Art for Wellbeing. Findings indicate that early interest in art leads to skill development and emotional expression, art facilitates nonverbal communication and specific adaptations are necessary to address sensory issues. The study also reveals that while art enhances autonomy and well-being, limited access and support often hinder participation in art activities. The implications suggest that enhancing support systems and opportunities for autistic individuals in the arts can significantly improve their quality of life and provide viable career paths. However, the study is limited by its qualitative nature and the small sample size, which may affect the generalizability of the findings.